Determinants of Indian retailers' attitude towards using mobile technology for supply chain coordination. Issue 4 (1st January 2012) - Khare, Arpita; Khare, Anshuman
In developing countries, coordinating supply chain activities through technology is not an easy task. The purpose of this research was to understand the Indian retailers' attitude towards the use of mobile technology for coordinating and communicating with suppliers and customers. Three main objectives emerged related to the retailers' use of mobile phones for supply chain decisions: supply chain integration, supply chain management and customer relationship management. The findings suggest that mobile technology provides easy accessibility, flexibility and convenience to the retailers for coordinating with supply chain members in a developing country like India.